Development of a REST API for Human Resource Information System for Employee Referral Management Domain Using the Express JS Framework and Node.js - Varinia Azkarin; Rangga Gelar Guntara; Oding Herdiana (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This paper presents the development process of a REST API for a Human Resource Information System (HRIS) focusing on employee referral management. The API was developed using the Express JS framework and Node.js, leveraging their powerful capabilities for efficient web application development. The HRIS serves as a centralized platform for managing employee referrals, tracking candidate progress, and optimizing talent acquisition. The article provides insights into the methodology, key features, and advantages of using the Express JS framework and Node.js for building such an HRIS. The results of the study indicate that the Express JS and Node.js frameworks have successfully developed a REST API for HRIS in the domain of employee referral management. This is evident from the black box testing results, which show valid outcomes for each tested request and response in every API endpoint.